مدى تأثر طرق الاعتراف المحاسبيب عناصر القوائم المالية بأهداف ممارسات إدارة الأرباح - دراسة ميدانية في الشركات المساهمة العامة في سورية- - يوسف علي; سميا ربيع (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدف البحث إلى دراسة أثر الاعتراف بعناصر القوائم المالية في ممارسات إدارة الأرباح, من خلال تحديد مفهوم الاعتراف بعناصر القوائم المالية, وتحديد معايير الاعتراف,وكيفية الاعتراف لكل عنصر من عناصر البيانات المالية على حدا وفقا لما جاء في المعايير الدولية لإعداد التقارير المالية ومعايير المحاسبة الدولية, كما يدرس هذا البحث طبيعة وماهية إدارة الأرباح, والدوافع التي تدفع الإدارة إلى ممارسة أنشطة إدارة الأرباح, والطرق التي تتبعها الإدارة عند ممارستها لأنشطة إدارة الأرباح, بهدف زيادة أرباحها أو تخفيضها أو الحفاظ على سلسلة مستقرة من الأرباح خلال فترة زمنية معينة, وتم اختبار فرضية البحثمن خلال الدراسة الميدانية المطبقة على عينة من الشركات المساهمة العامة في سورية مكونة من /20/ شركة، وقد توصلت الدراسة إلى أن إدارة المنشأة تقوم باستخدام القواعد المختلفة للاعتراف لكل عنصر من عناصر البيانات الماليةبهدف الوصول إلى الأرباح المستهدفة, كما توصلت الدراسة إلى ضرورة الحد من الحرية المتاحة للمدراء في استخدام الأحكام في اختيار قواعدالاعتراف عن المعلومات, وضرورة التقيد بمعايير موحدة لجميع الشركات. The research aims to study the impact of the recognition of the elements of financial statements in earnings management practices, by defining the concept of recognition of the elements of financial statements, and to identify the criteria for recognition, and how to recognize each of the elements of financial statements to an end, according to the International Financial Reporting Standards and International Accounting Standards, also studying this research nature and essence of earnings management, and motivations that drive management to the practice of earnings management activities, and the ways in which the management on the exercise of the activities of earnings management, in order to increase profits or reduce or maintain stable profits series during a certain period of time, Findhypothesiswastested throughfield studyapplied toa sample ofpublic shareholding companiesin Syriais composed of/ 20 /company. The study has found that the management of the facility are using different rules for the recognition of each of the elements of financial statements in order to reach the target profit, as the study found the need to limit the freedom available to managers in the use of Provisions in the selection rules for the recognition of information, and the need to comply with uniform standards for all companies.